2022
DOI: 10.3390/ani12162044
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal S100/Calgranulin Expression in Cats with Chronic Inflammatory Enteropathy and Intestinal Lymphoma

Abstract: Diagnosing chronic inflammatory enteropathies (CIE) in cats and differentiation from intestinal lymphoma (IL) using currently available diagnostics is challenging. Intestinally expressed S100/calgranulins, measured in fecal samples, appear to be useful non-invasive biomarkers for canine CIE but have not been evaluated in cats. We hypothesized S100/calgranulins to play a role in the pathogenesis of feline chronic enteropathies (FCE) and to correlate with clinical and/or histologic disease severity. This retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 80 publications
3
17
0
Order By: Relevance
“…Jejunal lymph nodes in cats with LGITL were significantly thicker (LGITL: median, 6.7 mm; range, 2.9‐12 mm; LPE: median, 4.2 mm; range, 1.8‐8.8 mm), significantly rounder and more hypoechoic compared with cats with LPE (Figure 2). 40 The same study showed that the presence of mild abdominal effusion tended to be associated with a final diagnosis of LGITL (45% in cats with LGITL vs 14% in cats with LPE) 40,94 . Specific lesions in liver and spleen that allow for differentiation of LPE from LGITL have not been reported in cats.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Jejunal lymph nodes in cats with LGITL were significantly thicker (LGITL: median, 6.7 mm; range, 2.9‐12 mm; LPE: median, 4.2 mm; range, 1.8‐8.8 mm), significantly rounder and more hypoechoic compared with cats with LPE (Figure 2). 40 The same study showed that the presence of mild abdominal effusion tended to be associated with a final diagnosis of LGITL (45% in cats with LGITL vs 14% in cats with LPE) 40,94 . Specific lesions in liver and spleen that allow for differentiation of LPE from LGITL have not been reported in cats.…”
Section: Resultsmentioning
confidence: 99%
“…Hypocobalaminemia frequently has been documented in cats with CE with a reported prevalence between 18% and 80% 40,47,67,73,75,86‐93 . In studies that compared serum cobalamin concentrations between cats with LPE and those with LGITL, the prevalence of hypocobalaminemia was reported to be significantly higher in cats with LGITL 40,67,88,89,94 . An increase in serum methylmalonic acid (MMA) concentration indicates cellular cobalamin deficiency and hence has been investigated in correlation with serum cobalamin concentrations in cats 87,88,95,96 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations